Продуктивність пагонів озимої пшениці за різного забезпечення мінеральним живленням - Жук, О.І. (Фактори експериментальної еволюції організмів, 2016)
Aim. The aim of this work was to study the influence of mineral nutrition on winter wheat stems productivity. Methods. Winter wheat (Triticum aestivum L.) cultivars ‘Mironivska 808’ and ‘Favoritka’ were grown on mixture of soil and sand in pots with capacity of 7.5 kg. Optimal plant mineral nutrition was N₉₀P₉₀K₉0, deficit supply was N₃₂P₃₂K₃₂. After maturing the ears length, quantity of grains in ear, and mass of 1000 grains were measured. Results were statistically analyzed with Microsoft Excel. Results. The length of winter wheat ears and grains quantity in ear of main and lateral stems was studied under optimal and deficit support of mineral nutrition. The higher quantity of grains was detected in main stems than in lateral ones under the optimal and deficit nutrition. The tillers have less grains then main stems under different mineral nutrition. The wheat cv. ‘Favoritka’ under deficit mineral nutrition was more productive than cv. ‘Mironivska 808’. Conclusions. It is shown that decreasing supply of nitrogen, phosphorus and potassium inhibited plants productivity of winter wheat cultivars ‘Mironivska 808’ and ‘Favoritka’ during pot experiment.